EXPLORING THE LINK BETWEEN CORPORATE STRATEGIES AND PERFORMANCE IN NAGPUR’S INFORMATION TECHNOLOGY SECTOR - Shah, Kalindi M; Dr. Manish Vyas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
IT is a quickly changing and complex catchment area, where successful business growth and being competitive can only be done using successful corporate strategies. This research investigates the relationship between corporate strategy and organizational performance in Nagpur district IT sector. Analysing and linking some of the more critical strategic factors, such as innovation, digital transformation, leadership effectiveness, market adaptability and human resource management and their positive effects on overall business performance. Using quantitative research, data was collected and analyzed through structured surveys across IT firms in Nagpur using statistical correlation approaches. By establishing the links among these constructs, findings of this research identify, and subsequently enrich, academic and business literature across IT domain by introducing key constructs that are determinants of strategic planning, operational efficiency, and financial performance. The paper is essential reading for industry leaders, policymakers, and researchers looking to optimize strategic decision-making processes and drive organizational success in the IT sector.